The Epidemiology of Hand, Foot and Mouth Disease in Asia: A Systematic Review and Analysis. Issue 10 (October 2016) - Koh, Wee Ming; Bogich, Tiffany; Siegel, Karen; Jin, Jing; Chong, Elizabeth Y.; Tan, Chong Yew; Chen, Mark IC; Horby, Peter; Cook, Alex R.
Abstract : Context: Hand, foot and mouth disease (HFMD) is a widespread pediatric disease caused primarily by human enterovirus 71 (EV-A71) and Coxsackievirus A16 (CV-A16). Objective: This study reports a systematic review of the epidemiology of HFMD in Asia. Data Sources: PubMed, Web of Science and Google Scholar were searched up to December 2014. Study Selection: Two reviewers independently assessed studies for epidemiologic and serologic information about prevalence and incidence of HFMD against predetermined inclusion/exclusion criteria. Data Extraction: Two reviewers extracted answers for 8 specific research questions on HFMD epidemiology. The results are checked by 3 others. Results: HFMD is found to be seasonal in temperate Asia with a summer peak and in subtropical Asia with spring and fall peaks, but not in tropical Asia; evidence of a climatic role was identified for temperate Japan. Risk factors for HFMD include hygiene, age, gender and social contacts, but most studies were underpowered to adjust rigorously for confounding variables. Both community-level and school-level transmission have been implicated, but their relative importance for HFMD is inconclusive. Epidemiologic indices are poorly understood: No supporting quantitative evidence was found for the incubation period of EV-A71; the symptomatic rate of EV-A71/Coxsackievirus A16 infection was from 10% to 71% in 4 studies; while the basic reproduction number was between 1.1 and 5.5 in 3 studies. The uncertainty in these estimates inhibits their use for further analysis. Limitations: Diversity of study designs complicates attempts to identify features of HFMD epidemiology. Conclusions: Knowledge on HFMD remains insufficient to guide interventions such as the incorporation of an EV-A71 vaccine in pediatric vaccination schedules. Research is urgently needed to fill these gaps.